Solvothermal Synthesis and Characterizations of Two Isomerism Cobalt Phosphite‐Oxalates with Varying Dimensions Using the Same Template from in situ Reaction. Issue 15 (31st July 2019) - Xiu, Zhijia; Jiang, Yansong; Wang, Honghao; Liu, Lu; Ma, Yike; Li, Na; Huang, Liangliang; Bi, Yanfeng
Abstract : Two novel cobalt phosphite‐oxalates with different frameworks, which are isomeric and of stoichiometry Co(H2 PO3 )(C2 O4 )· (C2 H8 N) (1 and2 ), were prepared under solvothermal conditions by in situ reactions. Single‐crystal X‐ray diffraction analysis reveals that1 crystalilizes in the triclinic system space group P 1 and2 crystallizes in the monoclinic system space group P 21 / n . Compound1 shows a 2D layered structure and2 presents a 3D open‐framework. Both structures are constructed with zigzag cobalt oxalate chains and [H2 PO3 ] – pseudopyramids. The solvent with different pH values and components plays an important role in the formation of the final structures of both compounds. Moreover, magnetic properties were also investigated. Abstract :